Effect of Photovoltaic Energy-Saving Window Factors on Building Heating Load Under Three Control Modes - Jiayi Li; Jianmei Wu; Hongpeng Xu (Buildings)
Photovoltaic (PV) glazing is widely used in the building sector for its power generation advantages. However, its low transmittance reduces solar heat gain, limiting energy-saving effectiveness in heating regions. To address this, the present study proposes a novel PV energy-saving window that reduces heating load by separately controlling its components—PV glazing, insulated shutter, and clear glazing—through three control modes: Mode 1 controls insulated shutter, Mode 2 controls insulated shutter and PV glazing, and Mode 3 controls insulated shutter and clear glazing. First, the energy-saving benefits of the window were confirmed through in situ testing. Next, using a validated model, the correlation between key factors and heating load was analyzed under the above three modes. Finally, the impact of configurations on heating load under the three control modes was clarified. The main findings are as follows: (1) When PV glazing is controlled, clear glazing layers become the primary factor influencing the heating load. (2) In Modes 1 and 3, the configurations have a greater impact on heating load, reducing it by 34.62% and 39.60%, respectively, while Mode 2 shows a reduction of 17.93%. (3) Mode 2 is the optimal control mode, confirming the effectiveness of controlling PV glazing to reduce heating load.